Inflation and attention thresholds - Oleg Korenok; David Munro; Jiayi Chen (Global Labor Organization (GLO), 2022)
One of the dangers of high inflation is that it can cause firms and households to pay close attention to it. This internalization of inflation can lead to an accelerationist regime, making inflation harder to control. We empirically assess the relationship between attention and the level of inflation for 37 countries. Our measures of attention are constructed either from internet search behavior or the popularity of inflation mentions on Twitter. We find evidence that attention thresholds do exist for the majority of countries in our sample. We also find interesting variability across countries.
Keywords: E31; E52; E70; 330; inflation; attention; threshold